The Spatial Analysis of the Average Household Size in the Countryside of Salah AI- Din Governorate in 2021 and Its Future Expectations - Jassim Aljburi, Asraa Ibrahim; shalal Fendi, Adel Taha (Journal of Tikrit University for Humanities, 2024)
It was found that the average size is in 2021 (6.6) individuals were recorded in AL-mutasim sub – district, while the lowest rate was recorded in the Tigris sub-district, which was (4.1) individuals. By 2030, the average of family size decreased to (6) people at the level of the governorate as a whole. The highest rate was recorded in AL-Mutasim sub-district, (9.4) individuals, and the lowest rate was recorded in the Tigris sub-district, which was (3.9) individuals. Due to the economic, social and demographic factors that affect the average family size in urban areas of the governorate which led to the tendency of family size towards miniaturization. The difference between the base year and the target year is (0.4) individual.